Comparison of the physical fitness traits of Azerbaijan and Iran senior Greco-Roman national wrestling teams - Rahmani, F.; Mirzaei, B. (Physical Education of Students, 2019)
Purpose: The aim of the present investigation was to compare of the physical fitness traits of Azerbaijan and Iran senior Greco-Roman national wrestling teams. Material: In this study, 10 elite wrestlers (age 27.7±3.5 years and training background 8.5±2 years) of the senior national wrestling team of Azerbaijan were measured in body composition attributes, muscular strength, muscular endurance, maximal oxygen consumption, flexibility, agility, speed, anaerobic power and explosive power and the results were compared to the national Greco-Roman wrestling team of Iran. Results: The results of this study, using t-test, showed that the mean of squats (P=0.013) and 40-yd sprint (P=0.004) in wrestlers of Azerbaijan`s team were significantly better than Iran`s average norm. However, the values of sit-ups (P=0.030), pull-ups (P=0.000) and 4×9-m shuttle run (P=0.024) the mean were significantly lower in the wrestlers of Azerbaijan compared to the norm of Iranian wrestlers. Conclusions: The results of the physical fitness tests determine the strengths and weaknesses of the training programs and provide practical guidance to coaches in order to assess the extent of wrestlers likely progress or slump.